Outlook 2010 advanced - Conway, Pamela; Safari eBooks ([S.l.] : CompuWorks, 2012)
"In this course you will learn how to subscribe to RSS news feeds and use the Outlook Social Connector to stay current with friends, colleagues and informational outlines. You will also learn how to manage your mailbox using Quick Steps, archiving, junk mail options, searching, and categories. Additionally you will create and work Journal entries, set permissions to share Outlook folders, create e-mail templates, and use mail merge to send personalized messages to groups of contacts. Finally, you will learn how to customize Outlook to fit your needs."--Resource description page.
Presenter, Pam Conway.
Title from resource description page (viewed Apr. 12, 2013).
Keywords: Microsoft Outlook; Time management -- Computer programs; Personal information management -- Computer programs; Electronic books